Social Determinants of Health: Perspective of the ALAMES Social Determinants Working Group - Oliva López Arellano; José Carlos Escudero; Luz Dary Camona (Social Medicine Publication Group, 2024)
Introduction The recent discussion of the social determinants of health, which has been promoted by the WHO as a way to approach global health conditions is neither a new nor a foreign subject for Latin American social medicine or collective health. Indeed, this approach to health derives from the principles of 19th century European social medicine which accepted that the health of the population is a matter of social concern, that social and economic conditions have an important bearing on health and disease, and that these relationships should be subjected to scientific enquiry. (Rosen, 1985:81) The specific socio-historical conditions of Latin America in the 1970's fostered the development of an innovative, critical, and socially-based based health analysis, which was seen in an evolving theoretical approach with deep social roots. (Cohn, 2003) This analysis calls for scientific work which is committed to changing living and working conditions and to improving the health of the popular classes. (Waitzkin y col. 2001; Iriart y col. 2002). From its beginning, this school of socio-medical thought recognized that collective health has two main areas of research: 1) the distribution and determinants of health and disease and 2) the interpretation, technical knowledge, and specialized practices concerning health, disease, and death. The goal is to understand health and disease as differentiated moments in the human lifecycle, subject to permanent change, and expressing the biological nature of the human body under specific forms of social organization, all this in such a way as to allow discussion of causality and determination. (Breilh y Granda,1982; Laurell, 1982). Latin American social medicine criticized biomedical and conventional epidemiological approaches for isolating health and disease from social context, misinterpreting social processes as biological, conceptualizing health phenomena in individualistic terms, and adopting the methodological procedures of the natural sciences